An instructional cycle for enhancing innovation-embedded employability. Issue 8 (4th November 2014) - Harry Matlay, Professor; Chang, Chi-Cheng
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The capability of innovation is a major component of high-education students' employability. The purpose of this paper is to introduce an instructional cycle specific to information technology-related disciplines that helps improve the students' innovation capability and their employability. Design/methodology/approach – Literature review, expert adviceand quasi-experiments are used. Instructional activities were developed out of the innovative instructional cycle proposed in this study, which was adjusted in line with the opinions of 30 experts. Teaching experiments were then conducted on 120 college students to understand how well that instructional cycle leads to improvements regarding each creativity indicator, and how feasible the cycle's employability enhancement approach is. Findings – This study concluded eight indicators of employable creativity: the sensitivity to problems, organizing/integration ability, complexity, originality, flexibility, novelty, fluency and the desire to create. Research limitations/implications – This study does not focus on how creative thoughts are used to form a mental model that makes students more flexible and adaptable in workplaces. Originality/value – The contribution of this study lies in successfully verifying this "cycle" proposed has positive, beneficial effects on shaping a student's employability.